The Indirect Effect of Emotion Regulation on Minority Stress and Problematic Substance Use in Lesbian, Gay, and Bisexual Individuals - Rogers, Andrew H.; Seager, Ilana; Haines, Nathaniel; Hahn, Hunter; Aldao, Amelia; Ahn, Woo-Young (Frontiers in Psychology, 2017)
Lesbian, gay, and bisexual (LGB) individuals report higher levels of problematic alcohol and substance use than their heterosexual peers. This disparity is linked to the experience of LGB-specific stressors, termed minority stress. Additionally, bisexual individuals show increased rates of psychopathology, including problematic alcohol and substance use, above and beyond lesbian and gay individuals. However, not everyone experiencing minority stress reports increased rates of alcohol and substance misuse. Emotion regulation (ER), which plays a critical role in psychopathology in general, is theorized to modulate the link between minority stress and psychopathology. However, it remains largely unknown whether ER plays a role in linking instances of minority stress with substance and alcohol use outcomes. To address the gap, the current study assessed 305 LGB individuals’ instances of minority stress, ER, and substance and alcohol use outcomes. We assessed the role of ER in problematic alcohol and substance use among LGB individuals using moderated mediation, where sexual minority status was entered as the moderator, and ER difficulties was entered as the mediator. The results indicated significant indirect effects of minority stress, through ER difficulties, on both problematic alcohol and substance use. However, there was no significant interaction with sexual orientation status, suggesting that ER may be important for all LGB individuals in predicting problematic alcohol and substance use. These results highlight the important role that ER plays between instances of minority stress and substance and alcohol use in LGB individuals, suggesting that ER skills may serve as a novel target for intervention.